IMPLEMENTASI SUPPLY CHAIN MANAGEMENT (SCM) UNTUK MENDUKUNG E-COMMERCE PADA PT. COLOMBUS BERBASIS WEB - Saputra, Muhammad Wisnu Aji; Firmansyah, Ada Udi (Jurnal informasi dan komputer, 2023)
Columbus is a store that offers customers a wide selection of electronics for purchase either cash or credit. PT. Columbus can be found at the address Jl. Ah. Nasution 21 Yosorejo in East Metro District, Metro City, Lampung. This research was conducted in the hope of helping PT. Columbus built a system to track and control their inventory more effectively through the use of Supply Chain Management principles. Store efficiency in moving inventory and generating sales will increase if Supply Chain Management is implemented. Combining convenience for customers, employees and suppliers. Supply Chain Management process design using the Unified Modeling Language. The MySQL database will be used for the Supply Chain Management system that has been planned and implemented using the PHP programming language and other languages ​​suitable for website-based system development. This Supply Chain Management method helps businesses become more organized, and can reduce the need for physical interaction between companies, customers and suppliers.